2017
DOI: 10.1159/000478520
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Cognitive Decline in Amnestic Mild Cognitive Impairment and Early-Stage Alzheimer Dementia: Mini-Mental State Examination versus Neuropsychological Battery

Abstract: Background/Aims: Although the Mini-Mental State Examination (MMSE), Clinical Dementia Rating-Sum of Boxes (CDR-SOB), and neuropsychological batteries are widely used for evaluating cognitive function, it remains elusive which instrument best reflects the longitudinal disease progression in amnestic mild cognitive impairment (aMCI) and probable Alzheimer disease (AD). We investigated whether changes in these three instruments over time correlate with loss of cortical gray matter volume (cGMV). Methods: We retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 32 publications
1
31
0
2
Order By: Relevance
“…In the present study, the MMSE score was observed to change early in short-term, marked disease progression. Considering its cost-effectiveness and sensitivity, this global cognitive functioning measure serves as one of the most effective instruments for monitoring patients with AD over time [1,9,10]. Our results also support previous reports that changes in the WMS-R delayed logical memory [31], visuospatial construction [39] and semantic fluency [40] scores are suggestive of disease progression in mild AD.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, the MMSE score was observed to change early in short-term, marked disease progression. Considering its cost-effectiveness and sensitivity, this global cognitive functioning measure serves as one of the most effective instruments for monitoring patients with AD over time [1,9,10]. Our results also support previous reports that changes in the WMS-R delayed logical memory [31], visuospatial construction [39] and semantic fluency [40] scores are suggestive of disease progression in mild AD.…”
Section: Discussionsupporting
confidence: 88%
“…Timely implementation of such measures might compensate, maintain, or enhance neuropsychological abilities, improve the quality of life of both patients and caregivers by reducing distress, depression, and psychological morbidity, facilitate planning of subsequent care, personal, financial and health-related decision-making, and delay nursing home admission of patients [4][5][6]. Although most studies monitoring longitudinal changes focused on the Mini-Mental State Examination (MMSE) [3,[7][8][9][10][11], the Clinical Dementia Rating-Sum of Boxes (CDR-SOB) [3,9,12], and the Alzheimer's Disease Assessment Scale-cognitive subscale (ADAS-Cog) [3,8,9,11,13,14], the most optimal instrument reflecting longitudinal disease progression in mild dementia of Alzheimer-type remains elusive [9]. In this framework, the hierarchy of functional loss measured by changes in ADL has been generally relegated to the background.…”
Section: Introductionmentioning
confidence: 99%
“…Instruments, such as the K-MMSE and the Alzheimer’s Disease Assessment Scale-cognitive subscale (ADAS-cog), have been mainly used in previous studies for measuring cognitive decline. However, they lack sensitivity in detecting mild degrees of cognitive dysfunction, which demonstrate ceiling effects in MCI [18]. We will use the full neuropsychological battery, the SNSB, which contains comprehensive and diverse tests with varying difficulties, to sensitively and accurately monitor changes in cognitive function [11].…”
Section: Discussionmentioning
confidence: 99%
“…So NTB is able to quantitatively evaluate 5 cognitive domains, including attention, working memory, language, visuospatial function, visual memory and executive function.31 And it has been considered as the most valid instrument for monitoring cognitive decline in aMCI and dementia associated with AD.32…”
Section: Methodsmentioning
confidence: 99%